Prevention and treatment of ecchymosis, edema, and fibrosis in the pre-, trans-, and postoperative periods of plastic surgery - Anny Chi; Angela Lange; Marcus Vinicius Thomé Nóra Guimarães; Celso Bilynkievycz dos Santos (Revista Brasileira de Cirurgia Plástica)
Introduction: Fibrosis, intense edema, and ecchymosis are complications that represent a great challenge to dermatofunctional physiotherapists in the postoperative period of liposuction and abdominoplasty. Here we aimed to propose a new approach in the pre-, trans-, and postoperative periods to prevent and minimize fibrosis, intense edema, and ecchymosis, thereby expediting the patient's recovery and reducing the number of required physiotherapy sessions. Method: This controlled clinical trial included 20 female patients aged 18-56 years who were divided into the control group (CG; n = 10) and experimental group (EG; n = 10). All were scheduled to undergo abdominoplasty or abdominal liposuction at least 7 days after enrollment. The two groups were evaluated preoperatively. The CG received care only from the 4th postoperative day, while the EG received care during the pre-, trans-, and postoperative periods. Results: The EG required fewer mean physiotherapy sessions (p = 0.0032) and had lower perimetry values on the 4th postoperative day (p ≤ 0.05) in the inframammary groove and iliac crest, lower mean resolution of fibrosis (p = 0.0058), and lower mean resolution of ecchymosis (p = 0.0002) compared to the CG. Conclusion: The findings of this unprecedented study indicate that treatment in the pre-, trans-, and postoperative periods reduces edema, ecchymosis, and fibrosis formation in the postoperative period. It also decreases the number of required physiotherapy sessions and accelerates patient recovery from abdominal plastic surgery.